Influência dos investimentos sociais na classificação de empresas no Índice de Sustentabilidade Empresarial da BMF&BOVESPA - Martins, Marília Novais da Silva Pereira (2014)
The global market stimulates competitiveness by seeking financial return. However, in order to obtain these financial returns, companies cannot act without considering criteria of corporate sustainability, without which companies will lose competitiveness. The BM&FBOVESPA brought great contribution to companies operating in the market through the ISE (Corporate Sustainability Index). Nevertheless, it is justified to question whether the group of variables that include social responsibility investments is sufficient to better classify a company in the ISE portfolio or whether the weight the ISE sustainability concept is multifocal whose emphasis would balance for all the concepts included in the triple bottom line. In order to verify this assumption, this study sought to establish the actual weight of the social dimension within the ISE through logistic regression drawing on appropriate sampling of participating and non-participating companies in the ISE 2011 and 2012 portfolios. It was demonstrated that there are no significant differences between groups justifying the classification or not in the ISE portfolio, based only on the variables of the social dimension, as well as after adding variables representing the financial. t was noticed, thus, that the social dimension is not relevant enough to differentiate the involvement or not of a company in the ISE classification.